A Case of Eight-and-a-Half Syndrome After Cessation of Heparin Treatment - Demir, Caner Feyzi; Ozdemir, Hasan Huseyin; Kapan, Oktay (Turkish Neurological Soc, 2010)
[Abstract Not Available]
Keywords: Heparin; brain stem infarctions